1999
DOI: 10.1073/pnas.96.23.13223
|View full text |Cite
|
Sign up to set email alerts
|

Origin and evolutionary relationships of giant Galápagos tortoises

Abstract: Perhaps the most enduring debate in reptile systematics has involved the giant Galá pagos tortoises (Geochelone nigra), whose origins and systematic relationships captivated Charles Darwin and remain unresolved to this day. Here we report a phylogenetic reconstruction based on mitochondrial DNA sequences from Galá pagos tortoises and Geochelone from mainland South America and Africa. The closest living relative to the Galá pagos tortoise is not among the larger-bodied tortoises of South America but is the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
162
1
11

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 163 publications
(182 citation statements)
references
References 34 publications
8
162
1
11
Order By: Relevance
“…Previous molecular studies (11,(14)(15)(16) of giant Galápagos tortoises revealed marked genetic differentiation among most populations and a general pattern of colonization from geologically older to younger islands. However, due to the recent age of the radiation and incomplete lineage sorting these surveys presented insufficient information about relationships among recently diverged lineages.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous molecular studies (11,(14)(15)(16) of giant Galápagos tortoises revealed marked genetic differentiation among most populations and a general pattern of colonization from geologically older to younger islands. However, due to the recent age of the radiation and incomplete lineage sorting these surveys presented insufficient information about relationships among recently diverged lineages.…”
mentioning
confidence: 99%
“…Giant Galápagos tortoises are the largest terrestrial chelonians in the world and represent the only surviving group of giant tortoises where evolutionary divergence is evident among populations (13). The group is monophyletic and is derived from a mainland South American lineage (14). The radiation is comprised of 11 extant and four extinct taxa endemic to different islands, or is restricted to each of Isabela's five major volcanoes (ref.…”
mentioning
confidence: 99%
“…are renowned both for their uniqueness and for their contribution to the development of Darwin's theory of natural selection (1). Fifteen formally described taxa of giant Galápa-gos tortoises are generally recognized, four of which are extinct from the islands of Floreana (G. elephantopus), Santa Fe (Geochelone sp.…”
mentioning
confidence: 99%
“…Pritchard (1996) suggested that the four southern Isla Isabela taxa do not warrant separate status. Caccone et al (1999) found that those populations lack genetic differentiation; but latter, Caccone et al (2002) found that microphyes (Volcan Darwin) and vandenburghi (Volcan Alcedo) are genetically distinct, and deserve separation; but they can not refute the suggestion that the two southern most subspecies are not genetically distinct.…”
Section: Family Cheloniidaementioning
confidence: 91%